Peran Guru PAI dalam Pengembangan Alat Evaluasi yang Mendukung Proses Pembelajaran yang Berkualitas - Rahmawati, Shintia; Tarsono, Tarsono; Nugraha, Mulyawan Safwandy (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Effectiveness in learning as a very important thing in determining success in the learning process, especially the role of the teacher himself. But in fact, there are some problems that occur during the learning evaluation process, students who keep asking questions, lack of motivation and students who are not careful in reading the available questions. Therefore, the purpose of this study is to find out the role of PAI teachers in developing evaluation tools that support a quality learning process. This study used a qualitative approach with an analytical descriptive model. The data collection technique used observation to class VI at SDN Sawahlega 02 with 32 students, interviews with the principal, PAI teacher and two students in class VI and documentation studies. The result is the role of PAI teachers in developing evaluation tools that support a quality learning process that has the effectiveness of students thinking critically and increasing learning motivation. The role of the teacher himself in carrying out learning evaluations is carried out per each material that has been carried out to achieve quality learning targets. In conclusion, the development of evaluation tools supports the role of PAI teachers to have a positive impact on achieving quality learning for students in class VI SDN Sawahlega 02.